LEVEL OF SAFE BEHAVIOR WITH THE IMPLEMENTATION OF HOT WORK PERMIT APPROACH IN PT BBB EAST JAVA - Rinawati, Seviana (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: The causes of the accident were dominant due to unsafe behavior and other causes due to unsafe conditions and the other factors, especially in the paper industry such as PT. BBB, East Java which has a high risk of fire and the level of workers awareness towards safe behavior so it needed the assessment of safe behavior level based on the implementation of hot work permit system at PT. BBB. Purpose: this study was to determine Level of Safe Behavior with The Implementation of Hot Work Permit Approach in PT BBB East Java. Method: This research used descriptive observational, which was research methods to describe the data of the result of research used information, interview and observation directly by conducting analysis on safe behavior information and hot work permit system at hot work. The technique of data collecting used observation and interview directly. The data obtained then discussed by comparing with existing regulations. Result: The research informed about the level of safe behavior in good category (70%) in the implementation of hot work permit system has the applicable regulations and based on the results 70-98% good category, but there were still obstacles in documentation system, PPE and punishment/reward. Conclusion: Good safety behavior was indicated by the implementation of hot work permit system is good, but there were still some obstacles which are must get a follow-up.